2008
DOI: 10.1016/j.psychres.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Attentional deficits in cocaine-dependent patients: Converging behavioral and electrophysiological evidence

Abstract: Although there are several reports of patients with cocaine dependence displaying cognitive deficits, the nature of their information processing deficits is not well characterized. In the present study, the attentional performance of cocaine-dependent patients (n = 14) was examined and compared with that of healthy control individuals (n = 15). Attention was assessed using an auditory oddball eventrelated task as well as the Continuous Performance Test (CPT; Identical Pairs version). The cocainedependent group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
5
27
1
5
Order By: Relevance
“…Estes trabalhos mostraram uma diminuição das amplitudes e aumento das latências dos potenciais evocados auditivos de média e longa latência entre usuários de drogas, mesmo em períodos de abstinência, o que também é observado em pacientes esquizofrênicos/com transtornos psiquiátricos e em pessoas que mostraram uma maior chance de desenvolverem problemas com drogas e álcool. Os achados alterados dos potenciais evocados auditivos de média e longa latência, nestes casos, sugerem uma inabilidade de filtrar estímulos sensoriais não relevantes, de atenção seletiva, de manutenção da memória de trabalho e de discriminação, bem como foram associados com a existência de maior impulsividade (21)(22)(23) . A análise das latências absolutas e interpicos dos potenciais evocados auditivos de tronco encefálico (PEATE) feita no presente estudo não revelou diferenças entre os grupos de usuários de drogas e o grupo controle.…”
Section: Discussionunclassified
“…Estes trabalhos mostraram uma diminuição das amplitudes e aumento das latências dos potenciais evocados auditivos de média e longa latência entre usuários de drogas, mesmo em períodos de abstinência, o que também é observado em pacientes esquizofrênicos/com transtornos psiquiátricos e em pessoas que mostraram uma maior chance de desenvolverem problemas com drogas e álcool. Os achados alterados dos potenciais evocados auditivos de média e longa latência, nestes casos, sugerem uma inabilidade de filtrar estímulos sensoriais não relevantes, de atenção seletiva, de manutenção da memória de trabalho e de discriminação, bem como foram associados com a existência de maior impulsividade (21)(22)(23) . A análise das latências absolutas e interpicos dos potenciais evocados auditivos de tronco encefálico (PEATE) feita no presente estudo não revelou diferenças entre os grupos de usuários de drogas e o grupo controle.…”
Section: Discussionunclassified
“…An effect size analysis concluded that cocaine's largest impact on cognition is evidenced by tests of attention, as well as visual and working memory (Jovanovski et al, 2005). An electrophysiological study of cocaine-dependent participants revealed a reduced amplitude in the P300 component, considered to reflect an impairment in attention and working memory functions, compared with controls (Gooding et al, 2008). Likewise, a study of 42 crack cocaineaddicted individuals demonstrated a general, mild level of cognitive impairment as measured by a battery of 16 different tests (Goldstein et al, 2004).…”
Section: Cocainementioning
confidence: 99%
“…Numerous studies showed alterations of CEP P300 in neurological and psychiatric diseases, as well as consequences of traumatic damages of the brain, that is, craniocerebral injuries . Different substances that cause addiction, from alcohol and nicotine to various opiates, lead to changes in cognitive functions, including changes in P300 parameters, due to brain damage (54)(55)(56)(57)(58)(59)(60). Moreover, with P300 testing, damage of cognitive functions resulting from taking different medicines, especially antiepileptic drugs, can also be monitored (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported changes in P300 amplitude and latency in cases of chronic consumption of nicotine, alcohol, as well as cannabis, opioids, cocaine, and ecstasy (Table 2) (8,(54)(55)(56)(57)(58)(59)(60).…”
Section: Review Of Literaturementioning
confidence: 99%